Relationship between Social Media Usage and Mental Health among Adolescents in the United States - White, William (American Journal of Computing and Engineering, 2024)
Purpose: The aim of the study was to assess the relationship between social media usage and mental health among adolescents in the United States. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This study suggest a correlation between excessive social media use and negative mental health outcomes such as depression, anxiety, and low self-esteem, others propose a more complex relationship influenced by various factors. Factors such as the type and frequency of social media use, individual characteristics, and the quality of online interactions play crucial roles. Moderate use of social media for positive interactions and support can be beneficial, fostering a sense of connection and belonging. However, excessive use, especially when it involves passive consumption or comparison with others, may contribute to feelings of inadequacy and isolation. Additionally, cyberbullying and exposure to unrealistic standards may exacerbate mental health issues. Implications to Theory, Practice and Policy: Social comparison theory, uses and gratifications theory and self-determination theory may be used to anchor future studies on assessing the relationship between social media usage and mental health among adolescents in the United States. Educational initiatives should be developed to promote digital literacy skills among adolescents, parents, and educators. Policymakers should work with social media companies to develop guidelines and regulations aimed at promoting responsible platform design and content moderation